Points of Convergence Between Biblical Education and Ki Hadjar Dewantara’s Educational Philosophy: A Philosophical Comparative Study - Lilik Kusnadi; Marthin S. Lumingkewas (Journal of General Education and Humanities, 2026)
This study aims to comparatively analyze the educational paradigms of the Bible and the thought of Ki Hadjar Dewantara in order to identify their points of convergence, fundamental differences, and the potential integration of both within the context of character education in Indonesia. Employing a qualitative approach with a philosophical comparative method, this research examines primary sources such as biblical texts and the works of Ki Hadjar Dewantara, as well as secondary sources including books on educational philosophy, theological journals, and historical studies of Ki Hadjar Dewantara’s ideas. Data collection techniques include documentation studies and literature review, while data analysis involves hermeneutic interpretation, holistic analysis, systematic comparison, and philosophical synthesis. The results of the study indicate that both paradigms share several important points of convergence, particularly in their emphasis on character formation, learner autonomy, teacher exemplarity, and a holistic view of the educational process. However, there are fundamental differences in their epistemological, ontological, and axiological foundations. Biblical education is rooted in divine revelation, views humans as the Imago Dei, and orients its goals toward piety and spiritual salvation. Conversely, Ki Hadjar Dewantara’s thought is grounded in natural and cultural laws, views humans as individuals who must be empowered, and emphasizes happiness, moral character (budi pekerti), and national identity as its primary goals. These differences also influence their respective educational methods: the biblical emphasis on teaching truth and spiritual formation contrasts with the among method of Ki Hadjar Dewantara, which prioritizes learning freedom and learner-centered guidance.